Intraspecies diversity of Cryptococcus laurentii (Kufferath) C.E. Skinner and Cryptococcus podzolicus (Bab’eva & Reshetova) originating from a single soil sample - Rhode, Owen H. J. (Stellenbosch : University of Stellenbosch, 2006)
Thesis (MSc (Microbiology))--University of Stellenbosch, 2005.